EFFECT OF REPEATED FIRING OF PORCELAIN FUSED TO METAL ON PORCELAIN COLOR CHANGE - Tarsilah, Tarsilah; Endang Prawesthi; Didik Marsigid (Journal of Vocational Health Studies, 2025)
Background: The color of the porcelain surface is the main criterion for achieving perfect aesthetics. A factor that influences the color is the amount of firing of the porcelain. Purpose: To determine the color change of porcelain after repeated firing four times. Method: The research specimens consisted of 6 metals coated with Classic porcelain and 6 metals coated with Noritake porcelain and were subjected to four firing stages, then each stage was fired four times. The color change value was measured using VITA Easyshade. Statistical analysis using ANOVA. Result: The Classic and Noritake groups experienced a significant increase in color change from 1st to 2nd burning and from 1st to 3rd burning with a p-value < 0.05. There is a significant difference in the color change value based on the repetition of porcelain firing with a significance value of 0.000 < 0.05. There is a significant difference in the color change value based on porcelain products with a significant value of 0.020 < 0.05. There is no significant effect between repeated firing on porcelain and porcelain products in affecting the color change value with a significance value of 0.143 > 0.05. Conclusion: Both product groups experienced an increase in color change from firing 1st to 2nd and from firing 1st to 3rd. There was no increase in color change from firing 2nd to firing 3rd. There are significant differences in color change values based on porcelain products and there is no significant effect between repeated firing on porcelain and porcelain products on affecting color change values.